PENGGUNAAN SIARAN LANGSUNG (LIVE) FACEBOOK SEBAGAI MEDIA KOMUNIKASI PEMASARAN (Studi Kasus Pada Toko Online Qiqah Shop di Makassar) - Imran Rosyadi S; Sumardi Sumardi; Erniwati Erniwati (Jurnal Inovasi dan Pelayanan Publik Makassar, 2023)
The selection of effective promotional media not only increases the sales of a product, but is also able to brand a product. With the increasing number of Facebook users and the number of online shops in Indonesia, the opportunity to increase product sales using social media platforms is getting bigger. The presence of the Qiqah Shop online store in Makassar was welcomed by the public, as seen from the increasing number of product orders through the live Facebook feature. The type of research used is qualitative research. The strategy applied by Qiqah Shop uses the Stimulus Response (SOR) theory and the marketing communication theory of Philip Kotler & Kevin Lane Keller (2012) that purchases are influenced by several factors such as advertising, product brand image, price offered and so on. The live video streaming feature on Facebook social media can increase user engagement, because when the live is going on, sellers and viewers can interact directly and communicate in two directions thanks to the comment feature provided in the live video streaming feature.